CD8+ mycosis fungoides clinically masquerading as alopecia areata. (8th September 2016) - Amin, Sapna M; Tan, Timothy; Guitart, Joan; Colavincenzo, Maria; Gerami, Pedram; Yazdan, Pedram
Abstract : A 33‐year‐old female with a 7‐year history of CD8‐positive hypopigmented mycosis fungoides (MF) involving the trunk and extremities presented with a large well‐defined alopecic patch on her frontal scalp. Clinically, this area resembled alopecia areata (AA) and was without hypopigmentation or erythema. A scalp biopsy revealed a non‐scarring inflammatory alopecia and a superficial band‐like atypical lymphoid infiltrate with prominent epidermotropism. Atypical, predominately CD8‐positive lymphocytes were seen surrounding and infiltrating the bulb portion of several hair follicles. Treatments for her MF lesions have included topical bexarotene, topical corticosteroids and phototherapy. Her alopecia has been treated with high potency topical corticosteroids and multiple intralesional triamcinolone injections with very minimal hair regrowth to date. Alopecia due to cutaneous lymphoma is an uncommon phenomenon but can occur in erythrodermic MF or Sezary syndrome. AA‐like changes have most often been reported in conventional patch/plaque stage MF and folliculotropic MF. In these cases, the atypical lymphoid infiltrate is comprised predominately of CD4‐positive lymphocytes. This is a rare report of a CD8‐positive MF causing AA‐like changes. This case highlights the importance of a scalp biopsy in patients with a history of cutaneous lymphoma presenting with alopecia in order to evaluate the nature of their hair loss.